Periode Waktu Inisiasi Anti-Retroviral Terapi (ART) Berhubungan dengan Perbedaan Outcome dan Tingkat Kadar CD4 pada Kasus HIV Positif - Wayan Citra Wulan Sucipta Putri; Anak Agung Sagung Sawitri; Komang Ayu Kartika Sari (Faculty of Public Health, Hasanuddin University, Makassar, 2018)
Early ART (Anti Retroviral Therapy) treatment at higher CD4 levels is believed to provide better outcomes.This study aims to determine the differences in outcomes and levels of CD4 levels based on the initiation periodof ART in HIV positive patients. This is a retrospective study, using secondary data to see differences in outcomes(CD4, morbidity, morbidity, lost to follow-up) of patients based on time-span status of ART initiation. The studypopulation was all HIV-positive patients who were or had undergone antiretroviral therapy in Denpasar City. Atotal of 312 patients were included in the study according to the criteria. The results showed that the proportionof subjects who had a CD4 cell rise of only 0-99sel/mm3 tended to be greater in the group who started ART morethan 12 weeks compared to those who started ART 12 weeks down (44.7% vs 36.7%). Vice versa, the proportionof subjects who had a CD4 increase ≥100 cells/mm3 was greater in the ART initiation group ≤12 weeks (73.3% vs55.3%) p=0.046. The proportion of subjects who died and lost to follow up was greater in the subjects who startedART over 12 weeks than the opposite (respectively 11% and 24.2% vs 5% and 12.7%, p=0.003). Significant differenceswere also seen, the proportion of subjects who were still on HAART was greater in the group of subjects whoinitiated HAART ≤12 weeks (64.8% vs 82.4%, p=0.003).